Higher economic growth in poor countries, lower migration flows to the OECD – Revisiting the migration hump with panel data - David Benček; Claas Schneiderheinze (World Development, 2024)
Comparing emigration rates of countries at different stages of economic development, an inverse u-shape emerges. Since the “migration hump” peaks at an average income of 6000 to 10 000 USD, economic progress in developing countries is often assumed to increase migration consistently. However, it is poorly understood to what extend country-level characteristics, individual incomes and other dimensions of development evoke this pattern, which limits its value for causal inference and concrete policy advice. In this paper we focus on the role of economic growth and investigate whether in developing countries emigration indeed increases with economic progress at shorter more policy-relevant time periods of up to 10 years. Using 35 years of data on migration flows to OECD destinations, we successfully reproduce the hump-shape in the cross-section. However, our more rigorous fixed effects panel estimations that exploit the variation over time robustly feature contrasting results: emigration rates fall as incomes increase. This finding holds independent of the level of income a country starts out at. In contrast to prevailing development emigration narratives, our results imply that rising individual incomes discourage emigration and hence conducive economic policies can reduce emigration. Our findings do not rule out that other slow-moving development dimensions such as educational advancement, demographic change, and structural economic transformation could still increase migration in the long term.
Keywords: F22; F63; O15; 330; International migration; Economic development; Development assistance